Improving reading comprehension skills using Know-Want-Learn (KWL) strategy in grade V of SDN 196/II Taman Agung, Bungo Regency - Ulya Desmawati; Reni Guswita (Himpunan Pengembang Kurikulum Indonesia, 2025)
Indonesian language systematically from elementary to higher education has an important meaning not only in strengthening national identity, but also in encouraging the effectiveness of communication and supporting national development. This study aimed to enhance the reading comprehension skills of fifth-grade students at SDN 196/II Taman Agung, Bungo Regency, where initial observations indicated low performance. The research employed a Classroom Action Research (CAR) methodology conducted over two cycles, following the Kemmis and McTaggart model, which includes planning, acting, observing, and reflecting stages. The subjects were 15 fifth-grade students during the second semester of the 2024/2025 academic year. Data collection instruments consisted of observation sheets for teacher and student activities, reading comprehension tests, and documentation. The findings revealed significant improvements across each cycle. Teacher activity improved from the